2019
DOI: 10.5897/ajmr2019.9105
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxigenic, enteroinvasive and enteropathogenic Escherichia coli in fish from experimental fish farm (Layo), Cte dIvoire

Abstract: The objective of this study was to know the sanitary quality of fish coming from Layo farm. Twenty fishes (Oreochromis niloticus), were selected in four ponds and Escherichia coli were isolated in gills and viscera according to microbiological methods. One hundred and twenty strains of E. coli were isolated, and their virulence was performed by polymerase chain reaction (PCR) using specific primers. Eleven (11) strains (9.16%) including 7 strains of gills (11.66%) and 4 strains of viscera (6.66%) had virulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…A previous study in Turkey, 60 % of E. coli from cage culture O. mykiss (Onmaz et al, 2020) (Prakasan et al, 2022). Few previous reports in West Africa pathotypes of E. coli from farm O. niloticus were screened with different genes; with a percent prevalence of 8.33% Shiga toxigenic E. coli (STEC), 3.33% EIEC and 31% EHEC and 28% Shigella was isolated from market fish in Houston, Texas, USA (Okyer et al, 2018;Kouadio-Ngbesso et al, 2019). In a previous study, the pathogenic E. coli was revealed in O. niloticus and water with different virulence genes in Egypt (Galal et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in Turkey, 60 % of E. coli from cage culture O. mykiss (Onmaz et al, 2020) (Prakasan et al, 2022). Few previous reports in West Africa pathotypes of E. coli from farm O. niloticus were screened with different genes; with a percent prevalence of 8.33% Shiga toxigenic E. coli (STEC), 3.33% EIEC and 31% EHEC and 28% Shigella was isolated from market fish in Houston, Texas, USA (Okyer et al, 2018;Kouadio-Ngbesso et al, 2019). In a previous study, the pathogenic E. coli was revealed in O. niloticus and water with different virulence genes in Egypt (Galal et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work [5] on the waters in the ponds of this experimental farm revealed their strong contaminations with faecal coliforms and Vibrio. Our recent studies conducted [6], revealed the presence of enteropathogenic, toxigenic and enteroinvasive strains of E. coli in the gills and viscera of fish Oreochromis niloticus caught in Layo ponds, an aquaculture station. The presence of multiresistant germs in environment has also been detected [7,8].…”
Section: Introductionmentioning
confidence: 99%